Felt - needs and financial coping mechanisms a case study in Molo Boulevard. - Laurea, Pearl Angelie Tan
The case study was done to provide a picture of slum life, most especially during this time of economic crisis. Besides, it was thought to be significant that a more recent study is made, not only to add to the existing body knowledge about slum but also to update policy makers and development planners of the condition of slum dwellers. Knowing their situation would be one way to urge the authorities to take action over the problems that plague the slum community at present., The objectives of the study are the following: to come with the present socio-demographic profile of slum dwellers in Molo Boulevard; To find out how they financially cope with the difficulties that plague them as caused by economic crisis; To determine the dwellers' felt-needs and other income-generating activities. The content of this study is limited only to the socio-demographic characteristics, felt-needs, as well as other income-generating activities, and since this is a case study, their results were relevant only to the forty five households in Molo Boulevard. Due to lack of time, the case study was conducted only for two months and a half. It was stopped right after the people's revolution because it might have affected the people and caused considerable changes in their way of life. The gathering of the data was done through participant observation, informal interviews and use of interview schedule. The student also took pictures. The locale of the study is a portion of the barangay of Molo Boulevard, a line of over crowded shanties along the dirty sea shore. All of the forty five households were subjects because the sampling was purposive. The average household membership was 4.5. Most of the dwellers came from neighboring barangays which were also slum communities, like Tanza and San Juan. They came to live in this community when they were relocated six years ago when the superhighway was constructed. Though they were employed workers in slum Molo Boulevard, yet they were mostly contractual and casuals. Besides, the dwellers could not engage in other jobs or occupations aside from these because of their low educational attainment and lack of skills and experience. The dwellers live in box-like structure called "barong-barong". These usually raised three to five feet above the ground to protect them from getting wet during high tide. Inside it were only the basic properties; no appliances; no toilet facilities; no electricity. (p)A change was noted in the household expenditure pattern of the dwellers between the period before 1983 and at present. The dwellers this time could no longer spare extra amount from their earnings on other household expenses. They could only afford to spend on food; but even then, they hardly could. They even came to the extent of adopting mechanisms such as eating once or twice a day or buying cheap and cooked food, just to be able to cope. (p)Because of this economic condition, the dwellers come up with their own account of felt-needs. These felt-needs were a product of their situation that enabled the dwellers to evaluate their needs and direct them to important and necessary ones. The felt needs of dwellers were food, job, house lot, clean surroundings, cooperation, health center, clothing pot, plates and medicines. The economic crisis has led some of the dwellers to engage in other income-generating activities plus their need to survive and be able to cope with present difficulties. These other income-generating activities were making stove, baking, carpentry, fishing, vending, driving, etc., and they signify financial coping. However, not all were in the capacity to engage in theses activities due to lack of knowledge and skills and lack of capital to start a business. Furthermore, the activities engaged by dwellers were just like their occupations which could not assure them of a good way out their economic difficulties, because they were poor quality, inadequate and offered low income. Training and organizing use of local resources are recommended for a more productive and succesful income generating activities. Training is done through setting up of informal sessions where specialized skills are being introduced and taught by a volunteer teacher or as recommended by the CD or Social Welfare Worker. Organizing use of local resources is administered through setting up an organization that would be in-charge to tap resources. (p)Nursey and medical services should be extended in the place. (p)To avoid confusion and chaos, community mapping and house numbering must be introduced. Furthermore this promotes community identification and solidarity. (p)If ever the development planners decide to put up projects in the community, they must see to it that proper methodology is emphasized and followed. Lastly, a consciencious, responsible and knowledgeable CD or Social worker should be assigned in Molo Boulevard.